Modelling Carbon Footprint, Emission, and Sequestration of Kenaf Cultivation and Fiber Processing and Utilization into Automotive Components - Hamdon A. Abdelrhman; M. T. Paridah; Tasneem A. Almaleeh; Khalina Abdan (BioResources, 2023)
This study aimed to model carbon footprint, carbon dioxide sequestration, and emissions from kenaf cultivation as well as utilization of core and bast as biomaterials in the automotive industries and their environmental implications. It also considers the selection of suitable processing methods to improve the environmental performance of automotive parts. The data were obtained from three areas, and each area was divided into three cultivated sub areas for the carbon footprint model. Data regarding the conversion of kenaf to fibre when using kenaf high decorticator machines were provided from Kenaf Processing and Marketing Centre (CMPC) in Malaysia. The results showed that the total estimated quantity of carbon footprint of kenaf cultivation in the studied areas as well as the farms was about 0.750 tonne CO2/tonne. In addition, the total estimated quantity of carbon sequestration of automotive components in the studied states as well as the district was approximately 180,000 tonne CO2/tonne/hectare/year in addition to carbon sequestered by soil in hectare of cultivated kenaf. The practices of kenaf cultivation, processing, and utilization into automotive components is essential for the environment and will assist in the mitigation of climate change risks.